(untitled) (Revista de História da UEG (REVHIST), 2020)
The heresies which arose in the 12th and 13th centuries, a period that is inserted in the low average age, are phenomena that puts into question the spiritual power of the Church, who decided to take some action in which ami since the use of the sacred scriptures until the projection of military conflicts to contain their advances and preserve their integrity. From the understanding of Nachman Falbel and Hilaire Belloc about the concept and some examples of heretical currents we understand its amplitude. Similarly, the analyzes carried out on the basis of theoretical in relation to power and splendor of the Church, as well as their reaction against the heretical movements that will drive the assimilation of this article. Therefore, we seek to understand this whole plot of the various facets that comprise the medieval spirituality. Keywords: Heresy. Church. Low Average Age.